2009
DOI: 10.1371/journal.pcbi.1000553
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing in the Differentiation of Human Embryonic Stem Cells into Cardiac Precursors

Abstract: The role of alternative splicing in self-renewal, pluripotency and tissue lineage specification of human embryonic stem cells (hESCs) is largely unknown. To better define these regulatory cues, we modified the H9 hESC line to allow selection of pluripotent hESCs by neomycin resistance and cardiac progenitors by puromycin resistance. Exon-level microarray expression data from undifferentiated hESCs and cardiac and neural precursors were used to identify splice isoforms with cardiac-restricted or common cardiac/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 62 publications
3
87
0
Order By: Relevance
“…Recently, it has been shown that the large repertoire of splice isoforms expressed in ES cells is gradually reduced in absolute number during neural differentiation (44). In addition, during both neural and cardiac differentiation, the specific repertoire of splice isoforms present in the pluripotent versus committed lineages changes (36). These changes in splice isoform repertoire imply that ES cells likely utilize their large and unique set of splice isoforms to sustain a pluripotent state.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the large repertoire of splice isoforms expressed in ES cells is gradually reduced in absolute number during neural differentiation (44). In addition, during both neural and cardiac differentiation, the specific repertoire of splice isoforms present in the pluripotent versus committed lineages changes (36). These changes in splice isoform repertoire imply that ES cells likely utilize their large and unique set of splice isoforms to sustain a pluripotent state.…”
Section: Discussionmentioning
confidence: 99%
“…Positive splicing indexes were associated mainly with genes with a high level of expression (P = 1.39 × 10 −22 ; hypergeometric test), whereas negative splicing indexes were present mostly in genes with medium or low levels of transcription (P = 2.04 × 10 −24 ) ( A and B), suggesting that the effect of canonical histone depletion on splicing depends on the transcription intensity. As a second tool for studying alternative splicing, we used AltAnalyze software (31). In this case, using the default parameters of the MiDAS algorithm, 875 probe sets with splicing defects were identified in 702 genes (Dataset S1).…”
Section: Slbp Depletion Disrupts Chromatin Structure and Alters Histonementioning
confidence: 99%
“…In addition, the study may provide an insight for regenerative medicine since cardiomyocytes cannot be reproduced in patients with ischemic damage. Our results are consistent with those obtained by Salomonis et al (Salomonis, Nelson et al 2009) that…”
Section: Mesendodermal or Cardiomyocyte Differentiationsupporting
confidence: 94%